Mentoring student teachers within Ireland’s further education and training sector - Deirdre Tinnelly (International Journal of Evidence Based Coaching and Mentoring)
This study explores the lived experiences of initial teacher education (ITE) mentors in the further education and training (FET) sector in Ireland. The literature suggests mentors support the professional formation of student teachers. However, mentoring relationships seem highly variable. At present the voice of mentors is underrepresented within Irish research. This interpretivist phenomenological analysis (IPA) study is based on semi-structured interviews with four mentors, and was underpinned by Bourdieu’s concepts of habitus, field, and capital. The findings suggest mentors perform wide ranging functions to support their student teacher, but not all mentors report actually benefit from performing the role.